2013
DOI: 10.1111/nhs.12078
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an electronic inpatient medication record in reducing medication errors in Singapore

Abstract: This study examined the effectiveness of an inpatient electronic medication record system in reducing medication errors in Singaporean hospitals. This pre- and post-intervention study involving a control group was undertaken in two Singaporean acute care hospitals. In one hospital the inpatient electronic medication record system was implemented while in another hospital the paper-based medication record system was used. The mean incidence difference in medication errors of 0.06 between pre-intervention (0.72 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
6
0
3
Order By: Relevance
“…Not all the interventional studies showed positive outcomes, however. In the study performed by Choo et al, an inpatient electronic medication record system was the intervention used to reduce ME, but the system was found to have little effect [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all the interventional studies showed positive outcomes, however. In the study performed by Choo et al, an inpatient electronic medication record system was the intervention used to reduce ME, but the system was found to have little effect [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The factors contributing to MEs were reported in 15 studies [ 12 16 , 19 – 25 , 27 , 31 , 32 ]. The most common ones are listed below; it is important to remember, however, that MEs usually arise from poorly designed work environments and systems rather than the individual performance of a single practitioner [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Erros envolvendo prescrições equivocadas não são alertados pelo BCMA e o eMAR, que operam a partir da correção pelo profissional para que o sistema funcione normalmente (28)(29) . Estudo realizado em algumas unidades hospitalares, sem a utilização do código de barras eMAR, demonstrou que a taxa de erros de medicação praticamente duplicou (11,5%) em relação às unidades que faziam uso (6,8%) (26) . Diferentemente das tecnologias citadas anteriormente, usadas na administração, a tecnologia RFID apresenta vantagens relacionada à praticidade de uso.…”
Section: Discussionunclassified
“…O Bar-Code-Assisted Medication Administration (BCMA) (23)(24)(25) e Personal Digital Assistant (PDA) (31) são sistemas de leitura de código de barras projetado para evitar erros de medicação na administração, podendo ser registrado pelo Electronic Medication Administration Record (eMAR) (26)(27) . of Things (IoT) (32) e o Near Field Communication (NFC) (34) permitem a intercomunicação destas informações.…”
Section: (5) Prescrição Duraunclassified
“…The study revealed there was no significant difference in the incidence of medication errors following the introduction of the electronic medication record system [8]. It suggested that further studies should be conducted to evaluate how this system can reduce medication error rates and improve medication safety.…”
Section: Literature Reviewmentioning
confidence: 95%